Analisis Dampak Asidifikasi Industri Semen PT X Metode Life Cycle Assessment (LCA) : Gate to Gate - Syadzadhiya Qotrunada Zakiyayasin Nisa'; Muhammad Riza Pahlevi (Prosiding ESEC, 2023)
The high potential for economic growth in the world has extreme threats from reduced energy supplies, use of fossil fuels, high dangerous gases and electricity prices. According to the European Commission in 2010, the cement industry is an industry that requires heat and electrical energy, so around 40% of all operational costs are spent on energy procurement. The cement industry is one of the largest contributors to air pollution in the world due to the level of energy consumption and potential dust emissions. This is a major factor in the source of air pollution. Air emissions from the cement industry contain chemicals that are harmful to health and the environment. Air pollution occurs if the composition of substances in the air exceeds specified thresholds. The presence of chemicals that exceed the limits can endanger health. One of the impacts that arise from the cement production process is the occurrence of acid rain or acidification. The aim of this research is to analyze and identify the stages that contribute the most to the potential impact of acidification, and present recommendations for improvements in an effort to reduce the environmental impact of the cement production process. The cement production process begins with the Kiln Mill, Clinker and Finish Mill stages. The method used in this research is Life Cycle Assessment. The scope used in this study is gate to gate. Data on production processes is analyzed using SimaPro 9.5 software. The Kiln Mill process is the stage in the cement production process that contributes to the largest acidification impact with a value of 0.556 kgSO2 eq/ton. The recommended alternative repair program is the use of Wet Type Flue Gas Desulfurization (FGD) and planting trees in industrial environments.